2021
DOI: 10.20452/pamw.16117
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid nodules with indeterminate cytopathology: a constant challenge in everyday practice. The effectiveness of clinical decisions using diagnostic tools available in Poland

Abstract: The study proves a low malignancy risk in Bethesda category III and IV thyroid nodules in the Polish population -6.7% and 11.3%, respectively. Universal referral for surgery of these indeterminate thyroid nodules leads to overtreatment, with patients unjustifiably being exposed to possible life-long complications. A concurrent analysis of the clinical risk factors and a thyroid nodule ultrasound pattern may be not sufficiently effective in refining the malignancy risk in thyroid nodule after obtaining an indet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Schneider et al 48 found that 30% of patients with CITNs had an insufficient initial thyroidectomy (under-or overtreatment). The study by Kotecka Blicharz et al 4 concluded that the vast majority of patients were overtreated by using TT instead of lobectomy resulting in postoperative complications such as hypoparathyroidism, recurrent laryngeal nerve palsy, and hypothyroidism. Some authors proposed "watchful waiting" as a strategic management option in certain patients with AUS/FLUS in the event of low epidemiological and radiological risk or according to the patients' preferences.…”
Section: Surgery the Extent Of Thyroidectomy (Tt Versus Hemithyroidec...mentioning
confidence: 99%
See 2 more Smart Citations
“…Schneider et al 48 found that 30% of patients with CITNs had an insufficient initial thyroidectomy (under-or overtreatment). The study by Kotecka Blicharz et al 4 concluded that the vast majority of patients were overtreated by using TT instead of lobectomy resulting in postoperative complications such as hypoparathyroidism, recurrent laryngeal nerve palsy, and hypothyroidism. Some authors proposed "watchful waiting" as a strategic management option in certain patients with AUS/FLUS in the event of low epidemiological and radiological risk or according to the patients' preferences.…”
Section: Surgery the Extent Of Thyroidectomy (Tt Versus Hemithyroidec...mentioning
confidence: 99%
“…The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC), which is commonly used, has a 97% sensitivity, a 50.7% specificity, a 3% falsenegative rate, and a 0.5% false-positive rate. 4 However, 25% of all FNAC diagnoses are in a gray zone of uncertain cytology; they are referred to as "cytologically indeterminate TNs" (CITNs). In these categories, no or little colloid is detected, and it is difficult to distinguish malignant tumors (follicular variant of PTC and follicular carcinoma) from benign lesions (nodular adenomatous goiter and follicular adenoma).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, many patients may have undergone unnecessary surgeries. Therefore, the challenge lies in distinguishing between benign and malignant ITNs before surgery [15]. Some research indicates that a single test can help in the management of ITNs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the challenge lies in distinguishing between benign and malignant ITNs before surgery. (15) Some research indicates that a single test can help in the management of ITNs. Carcinoembryonic antigen (CEA) and calcitonin are helpful for distinguishing medullary thyroid cancer from other types of thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%